1984
DOI: 10.1002/macp.1984.021850617
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of polylactones

Abstract: Temperature dependences of isochoric heat capacity, temperatures and enthalpies of physical transitions for polyglycolide, polyw-propiolactone), poly(y-butyrolactone), poly(bvaler0lactone), poly(8-caprolactone), polyundecanolactone, polytridecanolactone, and polypentadecanolactone were studied between 13,8 and (340 -550) K in a vacuum adiabatic calorimeter within a limit of experimental error of about 0,2%. From the results obtained the functions @ ( T ) -H o ( 0 ) , So(T), and G o ( T ) -@(O) were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 7 publications
5
53
1
Order By: Relevance
“…This feature improves the polymer flexibility and avoids the high rigidity of polyglycolide (T g ¼ 41 8C. [32] ). 2) A double melting peak, which is usually attributed to a recrystallization process that affects the proportion between populations of crystals with a different lamellar thickness, [33] can be observed depending on the crystallization conditions (i.e., second heating run of a hot crystallized sample).…”
Section: Synthesis and Characterization Of Poly[(4-hydroxybutyric Acimentioning
confidence: 98%
“…This feature improves the polymer flexibility and avoids the high rigidity of polyglycolide (T g ¼ 41 8C. [32] ). 2) A double melting peak, which is usually attributed to a recrystallization process that affects the proportion between populations of crystals with a different lamellar thickness, [33] can be observed depending on the crystallization conditions (i.e., second heating run of a hot crystallized sample).…”
Section: Synthesis and Characterization Of Poly[(4-hydroxybutyric Acimentioning
confidence: 98%
“…3 the value of Kg was found to be 8.11 x 104 K 2 in excellent agreement with the work of Phillips et al who reported a value of 8.00x 104 K 2 for a fraction of similar molecular weight. From the following data taken from the literature [24,25] (Ahf = 1.7 x 10 9 ergcm -3, T ~ --342 K, and bo=0.411 nm), ~c~ e was calculated to be 680 erg2cm -4. The necessity of taking the transport term Aq~/kT into account is made clear in Fig.…”
Section: Growth Rate Studymentioning
confidence: 99%
“…In the treatment of the data, the following expression was chosen for the transport term [16]: Aq~/kT = U*/R(T -T~) where U*= 1500 calmol 1 and Too = Tg -30. Tg is the glass transition temperature and was taken as 209 K [24]. From Fig.…”
Section: Growth Rate Studymentioning
confidence: 99%
“…It is well documented that large-membered lactones have little ring-strain and consequently are extremely difficult to polymerize by non-enzymatic methods. Several investigators have reported on polyesters derived from macrolactones [8][9][10][11] , but in all cases, no detailed description of the polymerization was given. Just recently, it was demonstrated clearly that 12 and 13-membered lactones could undergo ring-opening polymerization using an alkali metal methoxide as initiator 12) .…”
Section: Introductionmentioning
confidence: 99%